OPTIMIZATION OF DISTRICT COOLING SYSTEM DESIGN FOR RESIDENTIAL DISTRICT IN INDONESIAâS NEW CAPITAL - Khulafa Laksana, Afrendi
Currently, the use of air conditioning systems in Indonesia is increasing. This increase also results in an increase in building electrical energy consumption. Meanwhile, most of the electricity production in Indonesia still relies on coal-fired power plants. Burning coal itself produces greenhouse gas emissions that are harmful to the environment. Therefore, an efficient air conditioning system is a must to reduce the required electricity consumption. A system that is considered efficient is the district cooling system. In a previous study, a comparison was made between individual air conditioning and district cooling air conditioning systems. Although the results have been obtained that the district cooling system is more efficient than the individual system, design development still needs to be tried in order to obtain a design with the minimum electrical energy consumption and life cycle costs as possible. So, this study presented an optimization of the district cooling design. Optimization was executed by reselecting the air handling unit and redesigning the central cooling plant. Furthermore, dividing each zone into several subclusters and re-designing the piping system diameter were also applied to sizing the characteristic of the optimum pump. Based on the initial design, the calculated district cooling electricity consumption and the 25 years life cycle costs were 50,955,007 kWh/year and IDR 1,967,624,826,071.00, respectively. Meanwhile, after central chillers resizing and piping system optimization, the estimated electricity consumption reduced to 47,205,485 kWh/year with the 25 years life cycle cost of IDR 1,810,202,254,509.00. Thus, the design optimization was successfully executed with an electrical energy consumption efficiency of 7.36% and cost efficiency of 8.00%.